Everything you need to ace computer science and coding in one big fat notebook : the complete middle school study guide - Smith, Grant (Big fat notebook., 2020)
"The key concepts of coding and computer science easily digested and summarized, with critical ideas clearly explained, doodles that illuminate tricky concepts, and quizzes to recap it all. Kids will explore the concepts of computer science, learn how websites are designed and created, and understand the fundamentals of coding with Scratch, Python, HTML, and CSS."--